Geni jora by Abidah El Khalieqy : A study of feminism and the Malay-Indonesian society - Asmiaty Amat (Research Directions Journal, 2018)
The history of the women novel writers in Indonesia began with the novel Kalau Ta’Oentong, written by Selasih in 1933. This was followed by the discovery of a novel Kehilangan Mestika, written by a 17-year old writer, Fatimah H. Delais or Hamidah. The 1940s and 1950s saw the advent of more women novelists such as Arti Purbani, S. Rukiah, Suwarsih Djojoesposito, Waluyati Supangat, Nursiah Dahlan, Matiah Madijah and NH Dini. NH Dini became known in the 1960s but it was during the 1970s that her writing gained momentum. The following years welcomed women novelists such as Titie Said, Titis Basino, Marga T, Marianne Kattoppo, and Th Sri Rahayu Prihatmi. The Indonesian literary repertoire was further enhanced by women writers listed in the Angkatan 2000. These writers, for instance Ayu Utami, Abidah el-Khalieqy, Oka Rusmini, Djenar Maesa Ayu, Dewi Sartika and Ani Sekarnengsih, made significant contributions to Indonesian literature in the new millenium, with their strong opinions and criticisms.